Numerical investigation of gas entrapment in metal additive manufacturing using a quasi-sharp-interface particle method. (15th December 2022) - Duan, Guangtao; Sakai, Mikio
Highlights: Conventional diffusive-interface models might trigger spurious gas entrapment. A quasi-sharp-interface model (QSIM) was proposed for multiphase particle methods. The proposed QSIM can prevent the spurious breakup of sharp corners. The QSIM simulations showed that gas among granules did not cause porosity. Abstract: Porosity is a key issue for the parts fabricated by selective laser melting. However, the porosity formation mechanisms have not been fully clarified. In particular, the formation of small pores in fabricated parts from the gas among granules is controversial. The existence of sharp corners among molten granules is a key numerical challenge because the conventional diffusive interface model (DIM) might trigger spurious gas entrapment. To solve the problem, a quasi-sharp-interface model (QSIM) was proposed for the moving particle semi-implicit (MPS) method in this study. A new approach to calculate the interface area based on the local triangularization was proposed to accurately impose the surface-tension force in the QSIM. The bubble-rising simulation verified the capability of the QSIM to simulate topological changes of interfaces. The sharp-corner deformation problem demonstrated that the QSIM could effectively prevent unphysical breakup and the spurious gas entrapment. Thus, the QSIM was indispensable for reliably simulating the gas entrapment from the gaps among granules in SLM. Finally, the QSIM results indicated that the gas among granules was completely discharged when the granules melted. This suggested that the gas among granules did not cause small pores in the fabricated parts. This observation correlated with an experimental composition analysis of gas in pores. Graphical abstract: Image, graphical abstract